Persistence of Resident and Transplanted Genotypes of the Undomesticated Yeast Saccharomyces paradoxus in Forest Soil - James B. Anderson (American Society for Microbiology, 2018)
ABSTRACT One might expect yeasts in soil to be highly dispersed via water or insects, forming ephemeral, genetically heterogeneous populations subject to competition and environmental stochasticity. Here, we report persistence of genotypes of the yeast Saccharomyces paradoxus in space and time. Within 1 km2 in a mixed hardwood forest on scales from centimeters to tens of meters, we detected persistence over 3 years of native genotypes, identified by single nucleotide polymorphisms (SNPs) genome-wide, of the wild yeast Saccharomyces paradoxus growing around Quercus rubra and Quercus alba. Yeasts were recovered by enrichment in ethanol-containing medium, which measures only presence or absence, not abundance. Additional transplantation experiments employed strains marked with spontaneous defects in the URA3 gene, which also confer resistance to 5-fluoroorotic acid (5FOA). Plating soil suspensions from transplant sites on 5FOA-containing medium permitted one-step quantification of yeast CFU, with no interference from other unmarked yeasts or microorganisms. After an initial steep decrease in abundance, the yeast densities fluctuated over time, increasing in association with rainfall and decreasing in association with drought. After 18 months, the transplanted yeasts remained in place on the nine sites. In vitro transplantation experiments into nonsterile soil in petri dishes showed similar patterns of persistence and response to moisture and drought. To determine whether Saccharomyces cerevisiae, not previously recovered from soils regionally, can persist in our cold climate sites, we transplanted marked S. cerevisiae alone and in mixture with S. paradoxus in the fall of 2017. Five months later, S. cerevisiae persisted to the same extent as S. paradoxus. IMPORTANCE Saccharomyces yeasts are intensively studied in biological research and in their domesticated roles in brewing and baking, and yet, remarkably little is known about their mode of life in forest soils. We report here that resident genotypes of the yeast S. paradoxus are persistent on a time scale of years in their microhabitats in forest soils. We also show that resident genotypes can be replaced by transplanted yeast genotypes. The high inoculum levels in experimental transplantations rapidly decreased over time, but the transplanted genotypes persisted at low abundance. We conclude that, in forest soils, Saccharomyces yeasts exist at very low abundance and that dispersal events are rare.